An explicit stable Q-compensated reverse time migration scheme for complex heterogeneous attenuation media - Li, Songling; Shi, Ying; Wang, Weihong; Wang, Ning; Song, Liwei; Wang, Yinfeng (Frontiers in Earth Science, 2023)
Prestack reverse-time migration (RTM) is a popular imaging technique for complex geological conditions. Since the amplitude attenuation and velocity dispersion are common in seismic re-cordings. To image attenuated seismic recordings accurately, a robust migration algorithm with a stable attenuation compensation approach should be considered. In the context of the Q-compensated RTM approach based on the decoupled fractional Laplacians (DFLs) viscoacoustic wave equation, amplitude compensation can be implemented by flipping the sign of the dissi-pation term. However, the nonphysical magnification of image amplitude could lead to a well-known numerical instability problem. The explicit stabilization operator can rectify the amplitude attenuation and suppress the numerical instability. However, limited by the incon-venient mixed-domain operator, the average Q value rather than the real Q value is often used in the compensation operator, lowering the compensated accuracy of the migration image. To overcome this problem, we propose a novel explicit Q-compensation scheme. The main ad-vantage of the proposed compensation operator is that its order is space-invariant, making it more suitable for handling complex heterogeneous attenuation media. Several two-dimensional (2D) and three-dimensional (3D) synthetic models are used to verify the superiority of the pro-posed approach in terms of amplitude fidelity and image resolution. Field data further demon-strates that our approach has potential applications and can greatly enhance the resolution of seismic images.